Risk, courage, and women : contemporary voices in prose and poetry - Waldron, Karen A., 1945-; Labatt, Laura M., 1943-; Brazil, Janice H., 1951- (University of North Texas Press, 2007)
A collection of narratives, essays, and poems that includes an interview with Maya Angelou and pieces by Naomi Shihab Nye, Pat Mora, Rosemary Catacalos, and many others. Each work relates how women have demonstrated courage by taking a risk that has changed their lives.
Keywords: American literature -- Women authors.; Women -- Literary collections.; Courage -- Literary collections.; Risk-taking (Psychology) -- Literary collections.; Écrits de femmes américains.; Femmes -- Anthologies.; Courage -- Anthologies.; Prise de risque -- Anthologies.; LITERARY CRITICISM -- Women Authors.; American literature -- Women authors; Courage; Risk-taking (Psychology); Women; Women.; Womyn.; Risk behaviors.; Literary collections; Literature.; Littérature.